(untitled) (Journal of Industrial and Mechanical Engineering, 2020)
The 17 Sustainable Development Goals (SDGs) can be used as a general guideline so that nations or public and private organizations can focus their efforts and resources on obtaining concrete results in relation to obtaining a sustainable future. Of the 17 Goals, 169 targets were determined to be met before 2030, and in turn, a series of global indicators to measure their compliance. One of its main advantages is that they can be applied at different institutional levels from nations to small companies, guiding their actions. In this context, this line of research will seek to analyze the viability of the SDGs being used as tools in industries, under the hypothesis that companies have a relevant role, in terms of meeting the 2030 agenda, and that they could measure their progress in relation to the SDGs using environmental management indicators. This allows obtaining useful information for decision-making and to establish measures that enable both the reduction of environmental impacts and the identification of potential areas for improvement in the company.